2017
DOI: 10.1292/jvms.16-0528
|View full text |Cite
|
Sign up to set email alerts
|

A study on the efficacy of the recombinant <i>Yersinia</i> adhesin A vaccine against yersiniosis in the early phase

Abstract: Yersinia pseudotuberculosis (Y. ptb) is a zoonotic pathogenic bacterial species of the family Enterobacteriaceae and causes yersiniosis, an acute intestinal infection in humans and animals. Y. ptb is often implicated in lethal epidemics in zoo animals and reductions in the breeding population, but a valid prevention method has not been established. Therefore, this study aimed to develop a vaccine for yersiniosis control. The immunogenicity of one of the adhesion factors involved in pathogenic mechanisms of Y. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In this study, antimicrobial properties of the plant were examined and the extract of the O. pyrenacium showed antimicrobial effects against M. smegmatis, P. aeruginosa, S. aureus, and Y. pseudotuberculosis. Y. pseudotuberculosis is a pathogen that causes symptoms such as swelling of lymph nodes, septicemia, typhoidal clinical effects in humans (27). P. aeruginosa is a gram-negative bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, antimicrobial properties of the plant were examined and the extract of the O. pyrenacium showed antimicrobial effects against M. smegmatis, P. aeruginosa, S. aureus, and Y. pseudotuberculosis. Y. pseudotuberculosis is a pathogen that causes symptoms such as swelling of lymph nodes, septicemia, typhoidal clinical effects in humans (27). P. aeruginosa is a gram-negative bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that live Y. enterocolitica can (group 2), or just with phosphatebuffered saline (group 3-control). Survival rates after exposure to pathogenic Y. pseudotuberculosis were 100% (group 1), 60% (group 2), and 0% (group 3), respectively [95]. However, the recombinantly expressed YadA proteins did not induce mucosal immunity as measured by IgG secretion.…”
Section: Yersinia Spp Taamentioning
confidence: 91%
“…The authors concluded that YadA shows promising results as a vaccine component, but more research towards its safety, immunogenicity, and protective properties is necessary [95].…”
Section: Yersinia Spp Taamentioning
confidence: 99%
“…In fact, Tahir and Skurnik (2001) [93] found that immunizing mice with live bacteria raised antibodies against only epitopes located in the N-termini, whereas using inactivated bacteria raised antibodies against other epitopes as well. In addition, a study [94] found that mice immunized using a recombinant YadA vaccine had higher survival compared to those vaccinated with inactivated Y. pseudotuberculosis.…”
Section: Adhesinsmentioning
confidence: 99%